TAX AVOIDANCE AND FINANCIAL DISTRESS: A THREAT TO FIRM QUALITY? - Nicklaus Stanley; Luky Patricia Widianingsih (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
Tax avoidance has become an ongoing issue because it has a negative social impact on a country. Unlike previous studies that examined the direct effects of tax avoidance, this study adds financial distress as a moderating variable. In this regard, this study aims to obtain empirical evidence regarding the effect of corporate tax avoidance on firm quality. This study focuses on the consumer cyclical sector and uses secondary data obtained from firms’ financial reports. The analysis method used is moderated multiple linear regression analysis. The results show that tax avoidance has a significant negative effect on firm quality. Financial distress acts as a quasi-moderator, in which this condition strengthens the negative relationship between tax avoidance and firm quality, and has a positive effect on firm quality itself. Theoretically, this study enriches the tax avoidance literature by examining its impact on corporate quality, particularly in conditions of financial distress. Practically, the findings of this study also provide guidance for management to balance tax avoidance strategies with the internal conditions of the company.